(x-3)^3 – (x-3) .(x^2+3x+9).6(x-1)^2 Ngày mai e nộp rồi giúp e với

Question

(x-3)^3 – (x-3) .(x^2+3x+9).6(x-1)^2
Ngày mai e nộp rồi giúp e với

in progress 0
Rylee 3 tháng 2021-07-12T16:09:03+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-07-12T16:10:14+00:00

    Giải thích các bước giải:

    $(x-3)^3-(x-3)(x^2+3x+9)×6(x-1)^2$ 

    $=x^3-9x^2+27x-27-(x^3-27)×6(x^2-2x+1)$

    $=x^3-9x^2+27x-27-(6x^3-162)(x^2-2x+1)$

    $=x^3-9x^2+27x-27-6x^3(x^2-2x+1)+162(x^2-2x+1)$

    $=x^3-9x^2+27x-27-6x^5+12x^4-6x^3+162x^2-324x+162$

    $=-6x^5+12x^4+(x^3-6x^3)+(-9x^2+162x^2)+(27x-324x)+(-27+162)$

    $=-6x^5+12x^4-5x^3+153x^2-297x+189$

    $\text{Nếu đề này:}$

    $(x-3)^3-(x-3)(x^2+3x+9)+6(x-1)^2$ 

    $=x^3-9x^2+27x-27-(x^3-27)+6(x^2-2x+1)$

    $=x^3-9x^2+27x-27-(x^3-27)+6(x^2-2x+1)$

    $=x^3-9x^2+27x-27-x^3+27+6x^2-12x+6$

    $=(x^3-x^3)+(-9x^2+6x^2)+(27x-12x)+(-27+27+6)$

    $=0-3x^2+15x+6$

    $=-3x^2+15x+6$

    Học tốt!!!

    0
    2021-07-12T16:10:26+00:00

    Đáp án:

     

    Giải thích các bước giải:

    `(x-3)^3-(x-3).(x^2+3x+9)+6(x-1)^2`

    `=x^3-3.x^2` `.3+3.x.3^2-3^3-(x^3-3^3)+6.(x^2-2x+1)`.

    `=x^3-9x^2+27x-27-x^3+27+6x^2-12x+6`

    `=-3x^2+15x+6`.

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )